A broadband beam scanning antenna array based on substrate integrated coaxial line Butler matrix for Q‐band application. Issue 12 (12th August 2019) - Li, Xiuping; Hou, Yajing; Zhu, Hua; Qi, Zihang; Xiao, Jun; Cao, Cheng
Abstract: In this article, a broadband beam scanning antenna array is proposed in Q‐band attributed to miniaturized size, wideband and high integration. A patch antenna element is utilized with a back cavity, which is formed by metallic via holes and ground plane. A 1 × 4 series fed sub‐array is implemented by the patch element using multilayer PCB. Four symmetrical sub‐arrays and Butler matrix feeding network are used to form the antenna array with high gain and decrease side lobes. The Butler matrix is implemented by substrate integrated coaxial line, which provides low loss of around 0.09 dB/mm from 40 to 50 GHz. The measured antenna array bandwidth is 9.8 GHz (21.8%) under the condition of voltage standing wave ratio less than 2. The main beam of the antenna array in azimuth direction is tilted to −28.5°, −14.1°, 18.4° and 35.6° and the gains are 13.11, 13.88, 14.02 and 11.78 dBi at 45 GHz, respectively. Both the measured and simulated results agree well.